Craniofacial and upper airway morphological characteristics associated with the presence and severity of obstructive sleep apnea in Chinese children - Xu, Qiuping; Wang, Xiaoya; Li, Na; Wang, Ying; Xu, Xin; Guo, Jing (Frontiers in Pediatrics, 2023)
Abstract Objectives: To identify craniofacial and upper airway morphological characteristics associated with the presence and severity of obstructive sleep apnea (OSA) in children. Methods: This study consisted of 82 OSA children and 77 controls (age 5-10 y). All subjects had cephalograms and were divided into 5-7 age group and 8-10 age group. Cephalometric variables were compared between OSA children and controls, and hierarchical regression analysis was performed to examine the relationship between cephalometric variables and OSA severity [(expressed by obstructive apnea-hypopnea index (OAHI)] in different age groups. Results: Increased A/N ratio, narrowed posterior airway space, decreased SNA and SNB angle, and shorten ramus height were observed among OSA children in different age groups. In 5-7 age group, A/N ratio and lower gonial angle explained 40.0% and 14.7% of the variance in OAHI respectively. In 8-10 age group, BMI z-sore and A/N ratio explained 25.2% and 6.6% of the variance in OAHI, followed by lower gonial angle and hyoid-retrognathion distance (19.1% in total). Conclusions: Adenoid hypertrophy was a major factor associated with OSA in preschool children, whereas obesity replaced adenoid hypertrophy as the main contributor to OSA in the late childhood. Several craniofacial skeletal variables, such as SNB angle, ramus height, lower gonial angle and hyoid position, are also associated with the presence and/or severity of OSA, which could be used to help recognize children at higher risk for OSA.